How might we live? global ethics in a new century - Booth, Ken 1943-; Dunne, Timothy 1965-; Cox, Michael 1947- (Cambridge University Press, 2001)
This volume looks outward to the twenty-first century and to the dynamics of this first truly global age. It asks the fundamental question: how might human societies live? In contrast to the orthodoxies of academic Philosophy and International Relations in much of the twentieth century, which marginalised or rejected the study of ethics, the contributors here believe that there is nothing more political than ethics, and therefore deserving of scholarly analysis. By exploring some of the oldest questions about duties and obligations within and beyond humanly constructed boundaries, the essays help us ponder the most profound question in world politics today: who will the twenty-first century be for?